Efficiency Enhancement on Solid Oxide Fuel Cell system with anode off-gas recycle by evaluating entropy and exergy change - Hsin-Yi Lai; Hung-Ju Lin; Yen-Hsin Chan (Journal of Power Sources Advances)
The aim of this paper is to enhance the efficiency of the Solid Oxide Fuel Cell (SOFC) system through various system designs and parameters. To evaluate the effects of design configurations, the impact of high-temperature/low-temperature anode off-gas recycle (HT/LT-AGR) on system performance was investigated by calculating the entropy using the second law of thermodynamics. By analyzing the system with different AGR designs and considering the increasing entropy of heat components in the SOFC system, the efficiency calculations can be more practical and accurate.In this study, the working efficiency of the SOFC system with HT-AGR is 56.215 %, which is 4.7 % higher than with LT-AGR. The results show that the heat exchanger (HEX) experiences the largest increasing entropy during the power generation process due to the significant temperature difference. At the end of this project, a CO2 reformer will be used to optimize the system, decreasing the mole rate of CO2 and CH4 while increasing the mole rate of H2. Based on the simulation results, using a CO2 reformer can increase the mole rate of H2 by 3 %, improving the system efficiency up to 56.97 %.